Fucoidan treatment alleviates chilling injury in cucumber by regulating ROS homeostasis and energy metabolism - Lin, Duo; Yan, Ruyu; Xing, Mengying; Liao, Shuyuan; Chen, Jinyin; Gan, Zengyu (Frontiers in Plant Science, 2022)
Chilling injury is a major hindrance to cucumber fruit quality during cold storage. In this study, we evaluated the effects of fucoidan on fruit quality, reactive oxygen species homeostasis, and energy metabolism in cucumbers during cold storage. The results showed that, compared with the control cucumber fruit, fucoidan-treated cucumber fruit exhibited a lower chilling injury index and less weight loss, as well as reduced electrolyte leakage and malondialdehyde content. The most pronounced effects were observed following treatment with fucoidan at 15 g/L, which resulted in increased 1,1-diphenyl-2-picrylhydrazyl and hydroxyl radical scavenging rates and reduced superoxide anion production rate and hydrogen peroxide content. The expression and activity levels of peroxidase, catalase, and superoxide dismutase were enhanced by fucoidan treatment. Further, fucoidan treatment maintained high levels of ascorbic acid and glutathione, and high ratios of ascorbic acid/dehydroascorbate and glutathione/oxidized glutathione. Moreover, fucoidan treatment increased the activities of ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase, and glutathione reductase and their gene expression. Fucoidan treatment significantly delayed the decrease in ATP and ADP, while preventing an increase in AMP content. Finally, fucoidan treatment delayed the decrease of energy charge and the activities and gene expression of H+-ATPase, Ca2+-ATPase, cytochrome c oxidase, and succinate dehydrogenase in cucumber fruits. Altogether, our findings indicate that fucoidan can effectively enhance antioxidant capacity and maintain energy metabolism, thereby improving cucumber cold resistance during cold storage.